Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.1016/j.materresbull.2020.110821
|View full text |Cite
|
Sign up to set email alerts
|

Infrared absorbance of vertically-aligned multi-walled CNT forest as a function of synthesis temperature and time

Abstract: In this paper, the growth of optimized vertically aligned multi-walled carbon nanotube (VA-MWCNT) forests by LPCVD method for use in a large-area absorber in infrared detectors is presented. The effect of synthesis temperature (500−700°C) and time (1−10 min) on the optical absorption coefficient in the infrared (2−20 μm) is investigated by FT-IR measurement at various incident angles (15-80°). The structural properties of VA-MWCNT are characterized by SEM, TEM and Raman spectroscopy. Spectral measurements show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The carbon nanofiber microstructure is further confirmed by the Raman spectra presented in Figure 2g, which show three representative broadband peaks of carbon nanofibers centered at 1346, 1598, and 2835 cm −1 , which are respectively denoted as D (e.g., defects), G (e.g., crystalline graphitic carbon), and G ′ (e.g., overtone of D peak, more vitality with less graphitic sheets and defects). [27,28] The intensity ratio between the G peak and D peak is 1.42, implying a higher degree of graphitization of the CNFs, which is associated with the high-quality growth of CNFs. [29] All the atomic structure-based and microstructure analyses have demonstrated the successful growth of CNF activated by Ni catalyst embedded inside the commercial black anodized Al(6061) without the need to include further steps of additional catalyst deposition, thus enabling process simplification for further scaling-up.…”
Section: Resultsmentioning
confidence: 99%
“…The carbon nanofiber microstructure is further confirmed by the Raman spectra presented in Figure 2g, which show three representative broadband peaks of carbon nanofibers centered at 1346, 1598, and 2835 cm −1 , which are respectively denoted as D (e.g., defects), G (e.g., crystalline graphitic carbon), and G ′ (e.g., overtone of D peak, more vitality with less graphitic sheets and defects). [27,28] The intensity ratio between the G peak and D peak is 1.42, implying a higher degree of graphitization of the CNFs, which is associated with the high-quality growth of CNFs. [29] All the atomic structure-based and microstructure analyses have demonstrated the successful growth of CNF activated by Ni catalyst embedded inside the commercial black anodized Al(6061) without the need to include further steps of additional catalyst deposition, thus enabling process simplification for further scaling-up.…”
Section: Resultsmentioning
confidence: 99%
“…Previous attempts to develop broadband near-perfect absorption surfaces relied on the use of metamaterials, surface plasmons, 2D materials, or resonant optical cavities. [63][64][65][66][67][68][69][70] Common shortcomings of these efforts are narrow spectral bands and complex fabrication procedures with limited scalability for large-area applications. 29 Recently, several authors have reported alternative solutions based on the formation of one-dimensional nanomaterials such as carbon nanotubes, Si nanoarrays, Cu nanowires, and ITO nanowires.…”
Section: Please Do Not Adjust Marginsmentioning
confidence: 99%
“…[65][66][67][68] Common shortcomings of these efforts are narrow spectral bands and complex fabrication procedures with limited scalability for large-area applications 29 Recently, several authors have reported alternative solutions based on the formation of onedimensional nanomaterials such as carbon nanotubes, Si nanoarrays, Cu nanowires, and ITO nanowires. 29,[68][69][70] In our case, the characteristics of the supported nanotubes and nanotrees allow the straightforward use of these nanomaterials in a lithography-free process and on a broad variety of substrates without additional processing, patterning, or special optical arrangements.…”
Section: Optical Propertiesmentioning
confidence: 99%
“…Approaches based on thin-film interference filters using titanium (Ti) or silicon-carbide (SiC) layers [ 10 , 11 , 12 ] or porous metal layers [ 13 ] are reported. A more recent approach is based on absorption in areas coated with vertically grown carbon nanotubes (CNT) [ 14 , 15 ]. These approaches generally result in wideband absorption, which may be desirable in a general purpose pyrodetector, but often introduce an undesirable out-of-band sensitivity in a sensor system that is intended for spectrally selective operation.…”
Section: Introductionmentioning
confidence: 99%